How Does Support for Police Empowerment Change? Public Attitudes Toward Expanding Police Authority - Yaning Yue; Joselyne L. Chenane; Zedny Immatong (Criminal Justice and Behavior, 2026)
Police empowerment is often measured as a single attitude or as support for a single authority object at a time, leaving unclear how support changes as police authority expands. This study reconceptualizes police empowerment as a graded judgment, using a nationally representative survey of 1,000 U.S. adults to examine support across five increasingly expansive forms of police authority. A latent curve model distinguished respondents’ baseline willingness to empower the police from how that support changed as authority expanded. Support declined across the empowerment continuum. Procedural justice was associated with higher baseline support and a smaller decline as authority expanded, whereas satisfaction with local police was associated with higher baseline support but a steeper decline. A subsequent latent profile analysis identified three attitudinal profiles, showing that public attitudes toward police empowerment are heterogeneous in both degree and form. Implications for policy and future research are discussed.